Diagnosis and Management of Acute Aortic Syndrome: A Literature Review - Dedy Irawan; Novi Kurnianingsih; Djanggan Sargowo; Anna Fuji Rahimah (Universitas Brawijaya, 2021)
Acute aortic syndrome (AAS) is a potentially fatal disease that involves acute disruption of the aortic wall is. Several conditions such as intramural hematoma (IMH), aortic dissection (AD), penetrating atherosclerotic ulcer (PAU), as well as high mortality rates, are associated with this disease. Hypertension is an important risk factor, and patients often present with pain. AAS may be challenging to be evaluated, as it has a pre-test probability and several diagnostic tests. Computed Tomography Angiography (CTA) is essential in managing AAS. The significance of prompt diagnosis and treatment of AAS is emphasized further by the current developments in imaging techniques and therapeutic interventions, which ultimately lead to raised vigilance of this disease. Management of AAS included initial medical therapy and definitive therapy. In A type AAS, surgical intervention is the definitive therapy, while type B is managed definitively by endovascular or medical treatment.Keyword: Diagnosis, management, acute aortic syndrome.